2022
DOI: 10.1093/ehjcr/ytac233
|View full text |Cite
|
Sign up to set email alerts
|

Tip detection-antegrade dissection and reentry using intravascular ultrasound in chronic total occlusion intervention: first human case report

Abstract: Background It has been considered impossible to perform antegrade dissection and reentry (ADR) by simply puncturing with a guidewire using the intravascular ultrasound (IVUS) observation without the support of the Stingray system. Case summary A 78-year-old man suffered from effort angina pectoris due to a chronic total occlusion (CTO) lesion in the left circumflex coronary artery. A retry percutaneous coronary intervention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“… 5 Okamura et al reported the efficacy of IVUS-guided TD-ADR in CTO PCI. 6 , 7 Here, we present the first use of IVUS-guided TD-ADR in AMI. In CTO cases, target visualization by contralateral injection is very important.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Okamura et al reported the efficacy of IVUS-guided TD-ADR in CTO PCI. 6 , 7 Here, we present the first use of IVUS-guided TD-ADR in AMI. In CTO cases, target visualization by contralateral injection is very important.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 While performing this wiring, we first found in August 2021 that the TD method allows for antegrade dissection re-entry (ADR) because the wall between the subintima and the true lumen can be punctured at the intended part in an exactly vertical direction using the IVUS observation. We named this method “tip detection antegrade dissection re-entry (TD-ADR).” 6 …”
mentioning
confidence: 99%